CCR2 overexpressing gingiva mesenchymal stem cells provide high intestinal regeneration in a rat model of ulcerative colitis - Leyla Tekin; Deniz Genç (PLoS ONE, 2025)
Background/aims Ulcerative colitis (UC) is a chronic inflammatory disease affecting the colon. Mesenchymal stem cells (MSCs) are candidates for use in inflammatory diseases with their tissue regeneration and anti-inflammatory capabilities. Chemokine receptor overexpression on MSCs is an effective strategy for the migration of MSCs into inflammatory tissue in high amounts. In this study, the anti-inflammatory and regenerative effects of genetically CCR2 overexpressed gingiva MSCs (GMSCs) on the inflamed colon in UC were studied. Materials and methods GMSCs were transduced with a lentiviral vector for CCR2 overexpression. The UC experimental model was induced with a single intrarectal administration of 4% w/w acetic acid. Colon tissues were analyzed for IFN or IL-17 secreting CD4+  T lymphocytes via flow cytometry and lymphocytic infiltration, fibrosis, and ulcers by histopathologic evaluation. Homing analysis of GMSCs was done by analyzing fluorescence intensity under the fluorescence microscope. Results GMSCs and CCR2+GMSCs equally downregulated colonic IFN-γ or IL-17 secreting CD4+ T lymphocytes ratios compared to the untreated group (p < 0.05). Fluorescence intensity of labeled cells was significantly high in colon tissues of CCR2+GMSCs administered rats (61.2 ± 13.7%) compared to GMSCs administered rats (19.6 ± 9.8%) (p < 0.05). In addition, mucosal integrity significantly increased and fibrosis and ulcers notably decreased in CCR2+GMSCs administered rats compared to GMSCs administered rats (p < 0.05). Conclusion The overexpression of CCR2 on GMSCs increases migration to the inflammatory colon tissue, which has a high regenerative effect in UC. Overexpression of CCR2 on GMSCs may be an alternative to cellular therapies in UC.